The fast800 diet : discover the ideal fasting formula to shed pounds, fight disease, and boost your overall health - Mosley, Michael, 1957- (Atria Books, 2019)
Millions of people worldwide have lost weight and reversed disease using Dr. Mosley<U+2019>s The FastDiet, which revealed the incredible power of intermittent fasting. Clinical studies show that fasting not only helps you lose weight fast, but also improves blood sugar levels and heart health, boosts brain health and function, and is even proven to reduce the risk of cancer recurrence. Drawing on the latest research and his personal experience gaining and then losing 14 pounds, “the world<U+2019>s top gut health guru” (Dr. Barry Marshall, winner of the Nobel Prize for Medicine) returns with an even more effective<U+2014>yet easier to follow<U+2014>diet plan designed to reap maximum fasting benefits. The Fast800 Diet pinpoints the ideal fasting calorie count for health and weight loss: 800. Built around a more manageable 800-calorie fasting day<U+2014>whether that<U+2019>s 800 calories every day until you achieve your goals, or 800 calories twice a week<U+2014>Dr. Mosley<U+2019>s powerful three-phase program is designed to supercharge weight loss and fast-track a healthier life.